PERBANDINGAN KEMAMPUAN KOGNITIF BERDASARKAN KELOMPOK USIA PADA LANSIA DI DESA BAKUNG KECAMATAN KANOR KABUPATEN BOJONEGORO TAHUN 2014 - RAHMAWATI, RAHMAWATI; SYA'DIYAH, SITI NURUL; ASHARI, ACHMAD (Asuhan Kesehatan : Jurnal Ilmiah Ilmu Kebidanan dan Keperawatan, 2015)
Abstract The aging process experiebced by the edelry, the elderly result ini hanges that cause the elderly has decreased the work function of the brain/cognitive decline. Difference of age cause the existence of difference in behaviour, attitude, other personal characteristic and value. The cognitive function retreating can in the form of easy to forget to demensia. Target of this research is to analyze the compararison cognitive abilities in the elderly age gorup based in the village of daffodils district Bojonegoro Kanor 2014.This type research is comparative study of the  analytical research. Its population is around the elderly in the village of daffodils in April 2014 as many as 259 people, with a total sample of 155 people, who met the inclusion criteria by using simple random sampling. How to capture the data with a questionnaire which was the in editing, coding, scoring, tabulating and analyzed the data with the Kruskal-Wallis test, with significance level ? = 0,05. The result show the majority of respondents were aged 45-59 cognitive ability to function perfectly as many as 80 people (100%), and the majority of respondents were aged > 90 years of severe cognitive abilities serve as many as 4 people (100%). From the kruskal-wallis statistical test with value : 0,05. Value obtained : 0,000 < ( 0,05), so H0 is rejected. Its conclusion there are difference cognitive ability in the elderly age group based in the village of daffodils district of Bojonegoro Kanor 2014. So expect families who care for the elderly to give love to the elderly, be friendly, do not make anggry elderly and show appearances are alwas ready to help the elderly. Keywords : Age, elderly, Cognitive, Ability.  Abstrak Proses penuaan yang dialami oleh lansia, mengakibatkan lansia mengalami perubahan yang menyebabkan lansia mengalami penurunan fungsi kerja otak/penurunan fungsi kognitif. Di Desa Bakung pada lansia yang baru berumur 60 tahun banyak dijumpai lansia mengalami penurunan fungsi kognitif terutama terkait dengan dimensi waktu terutama untuk mengingat tanggal dan bulan. Tujuan penelitian ini adalah menganalisa perbandingan kemampuan kognitif berdasarkan kelompok usia pada lansia di Desa Bakung Kecamatan Kanor Kabupaten Bojonegoro tahun 2014.Jenis penelitian ini adalah analitik jenis study komparasi. Populasinya adalah seluruh lansia di Desa Bakung pada bulan April 2014 sebanyak 259 orang, dengan jumlah sampel sebanyak 155 orang. yang memenuhi kriteria inklusi dengan menggunakan simple random sampling. Cara pengambilan data dengan kuesioner yang kemudian di editing, coding, skoring, tabulating dan dianalisa data dengan uji Kruskal Wallis, dengan tingkat kemaknaan ? = 0,05.Hasil penelitian menunjukkan mayoritas responden yang berumur 45-59 kemampuan kognitifnya berfungsi sempurna yaitu sebanyak 80 orang (100%), dan mayoritas responden yang berumur > 90 tahun kemampuan kognitifnya berfungsi sedang yaitu sebanyak 4 orang (100%). Dari uji statistik  Kruskal Wallis dengan nilai a : 0,05. Didapat nilai r : 0,000 < a (0,05), jadi H0 ditolak.Kesimpulannya ada perbedaan kemampuan kognitif berdasarkan kelompok usia pada lansia di Desa Bakung Kecamatan Kanor Kabupaten Bojonegoro tahun 2014. Sehingga diharapkan keluarga yang merawat lansia untuk memberikan kasih sayang pada lansia, bersikap ramah, tidak membuat marah lansia dan menunjukkan penampilan yang selalu siap untuk membantu lansia. Kata Kunci : Usia, Lansia, Kemampuan, Kognitif